1989
DOI: 10.1111/j.1439-0442.1989.tb00739.x
|View full text |Cite
|
Sign up to set email alerts
|

The Activities of Phosphatases and Aminotransferases in the Epithelium of the Small Intestine and Caecum of White Rock Cockerels During Starvation

Abstract: Summary Alkaline phosphatase (ALP, EC 3.1.3.1), acid phosphatase (ACP, EC 3.1.3.2), aspartate aminotransferase (ASAT, EC 2.6.1.1) and alanine aminotransferase (ALAT, EC 2.6.1.2) were measured in the mucosal homogenates of the duodenum, jejunum and caecum of full‐fed (control), starved and re‐fed White Rock Cockerels. Starvation caused a significant (p 0.05) increase in the activity of ACP in all three segments of the intestine. Subsequent re‐feeding brought the activity back to the control level. In contrast A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1
1

Year Published

1996
1996
2003
2003

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
2
1
1
Order By: Relevance
“…Moreover, knowledge about this enzyme in birds has not changed much in the past 14 yr (see reviews in Duke 1986 andDenbow 2000). Accordingly, alkaline phosphatase activity falls in the intestine during starvation and is partially restored by refeeding in cockerels (Majumdar and Panda 1989), though this pattern was never reported in birds' plasma before this study.…”
Section: Recovery Periodcontrasting
confidence: 55%
“…Moreover, knowledge about this enzyme in birds has not changed much in the past 14 yr (see reviews in Duke 1986 andDenbow 2000). Accordingly, alkaline phosphatase activity falls in the intestine during starvation and is partially restored by refeeding in cockerels (Majumdar and Panda 1989), though this pattern was never reported in birds' plasma before this study.…”
Section: Recovery Periodcontrasting
confidence: 55%
“…La PA est localisée dans la bordure en brosse des microvillosités de la muqueuse intestinale et le poids sec de cette muqueuse, ainsi que sa teneur en PA, sont abaissés de J3 à J7 lors de diverses infections coccidiennes (Allen, 1987). Chez le poulet, la mise à jeun provoque à elle seule une chute de la PA dans la muqueuse intestinale (Allen, 1987;Majumdar & Panda, 1989). La chute de la PA plasmatique est cependant supérieure chez les sujets infectés à celle des sujets pair-fed (Yvoré et al, 1972).…”
Section: Discussionunclassified
“…Observations of the intestinal AP indicates that its activity is also directly related to the presence and the amount of food in the alimentary tract. It has been demonstrated that AP activity is closely related to the day-night fluctuation of food intake (Martinková et al 2000) and decreased after fasting in neonatal (Baker et al1987) and adult animals (Majumdar and Panda 1989). On the other hand, food restriction had an opposite effect i.e.…”
Section: Discussionmentioning
confidence: 98%